Chemosensitivity of three patient-derived primary cultures of canine pericardial mesothelioma by single-agent and combination treatment - Nabeta, Rina; Kanaya, Ami; Elbadawy, Mohamed; Usui, Tatsuya; Furuya, Tetsuya; Suzuki, Kazuhiko; Uchide, Tsuyoshi (Frontiers in Veterinary Science, 2023)
Introduction: Canine mesothelioma is a rare malignant tumor that mostly affects body cavities, such as the pericardial and pleural cavities. Chemotherapy plays a crucial role in the treatment of canine mesotheliomas. We aimed to compare the antitumor effects of single-agent and combination chemotherapeutic agents on patient-derived primary cultures of canine pericardial mesothelioma established in this study. We planned to generate xenograft models for future studies. Material and methods: Effusion samples were collected from three dogs with histologically diagnosed pericardial mesothelioma and used for primary culture. Cultured cells were characterized by immunostaining for pan-cytokeratin AE1/AE3, vimentin, Wilms' tumor suppressor gene 1 (WT1), and cytokeratin 5 (CK5). To assess the tumorigenic properties of cells in the effusion and generate a xenograft model, the cell suspension was injected into a severe combined immunodeficient (SCID) mouse either subcutaneously (SC) or intraperitoneally (IP). Lastly, chemosensitivity of established primary cultures against four drugs, doxorubicin, vinorelbine, carboplatin, and gemcitabine, by single-agent treatment as well as combination treatment of carboplatin at a fixed concentration, either 10 or 100 µM, and gemcitabine at different concentrations ranging from 0-1000 µM was assessed by cell viability assay. Results: Primary cultures were successfully generated and characterized by dual positivity for AE1/AE3 and vimentin and positive staining for WT-1 and CK5, confirming the mesothelial origin of the cells. In the xenograft models, SC mouse developed a subcutaneous mass, whereas IP mouse developed multiple intraperitoneal nodules. The masses were histopathologically consistent with mesotheliomas. The chemosensitivity assay revealed that carboplatin had the highest anti-tumor effects among the four tested single-agent treatments. Furthermore, carboplatin at 100 µM combined with gemcitabine at clinically relevant doses demonstrated the augmented anti-tumor effects compared to single-agent treatment. Discussion and Conclusion: Primary cultures and xenograft models generated in this study could be useful tools for in vitro and in vivo studies of canine mesothelioma. Carboplatin is a highly effective chemotherapeutic agent against canine mesothelioma when used as a sole agent and in combination with gemcitabine.